Issues and Different Forms of Federal Systems: An Analytical Study - Kandel, Professor Ishwori Prasad (Dhaulagiri Journal of Contemporary Issues, 2025)
The study, titled “issue and challenge of federalism” provides and focus on the critical analysis of the federal systems. It explores their fundamental principle, comparative politics, and implications for governance and sustainability. The research identifies the principle and types of government. The objective of this research is to generate the political ideology based on the federal system and its base foundation and issues and challenges. The study highlights the factors of federalism such as state system. Federacy in term of methodological paradigm, the doctrinal method is applicable on the basis of its nature of data collection. The secondary data and information has been taken from the various scholarly works, based on, different forms of federal system based on its origin, design and jurisdiction and the types of government and its constitution. The findings reveal significant merits and demerits of federal systems. Federal systems are recognized for their ability to maintain rules and regulations across the entire country, ensuring consistency and simplifying governance. In contrast, federal systems distribute power between central and regional governments, promoting regional representation and flexibility but potentially leading to inefficiencies and conflicts over jurisdiction.